Respostas

2014-06-05T02:40:25-03:00
1) 3x² - 7x + 2 = 0

a = 2       b = - 7       c = +2
Δ = b² - 4.a.c
Δ = (-7)² -4.(2).(+2)
Δ = + 49 - 16
Δ = 33

x = - b 
± √Δ
          2.a
x = - (-7) ± √33
            2.2
x = + 7 ± 33 
           4
x'= 7 + 
√33
          4         
x"= 7 -
√33   = 
        4          

S[(7-√33/4) , (7+√33)/4]

2) x² - 6x + 9 = 0

soma = 6       x1 = 3
produto = 9    x2 = 3

3) x² + x - 12 = 0

soma = 1            x1 = 4
produto = - 12      x2 = - 3

4) 2x² - 7x + 3 = 0
 
Δ =(7)² - 4.(2).(3)
Δ =49 - 24
Δ = 25  

x = 
 \frac{-b +/- √Δ }{2.a}
x =  \frac{7 + 5}{2.2}
x =  \frac{12}{4}  
x = 3

x =  \frac{7 - 5}{2.2}
x =  \frac{2}{4}
x = 0,5

5) x² + 6x + 10 = 0

soma = -6        
produto = 10